Deteksi Cemaran Mikroba Patogen, Sanitasi dan Hygiene Pada Pedagang Sate Lilit Ayam di Pantai Sekitar Pura Rambut Siwi Jembrana - Nigraha, I Gst km Rahendra Indrya; darmayanti, Luh Putu Trisna; hatiningsih, Sayi (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2025)
Sate lilit is typical Balinese foods made from meat that is mashed with the addition of Balinese spices. Meat is one of the food ingredients that has a high moisture content and there is water activity) in it, has a neutral pH, nutritional content such as fat and protein so that it is susceptible to contamination by E. coli and S. aureus microbes. This research aims to find out the hygiene and sanitation conditions of the traders, find out the presence of Escherichia coli and Staphylococcus aureus on satay . This research used a completely randomized design with 2 repetitions, sampling using survey techniques and total sampling. Data were presented in tabular form and analyzed descriptively total microbes, coliforms, Escherichia coli , Staphylococcus aureus and analyzed using ANOVA in the moisture content test. Parameters observed were total microbes, coliform, E. coli , S. aureus and moisture content. The results showed that 67% of the morning samples, 100% of afternoon and evening samples did not meet the requirements for total microbes (< 1 x 10 6 colonies/g), 100% of the samples were positive coliform, 100% of the samples did not meet the requirements for E.coli (< 1 x 10 colonies/g), 100% samples had met the requirements for S. aureus in the morning, afternoon and evening (< 1 x 10 4 colonies/g), 58.75% highest moisture content value in the afternoon sample, 37.43% lowest moisture content value in morning sample. The sanitation practices satay lilit sellers are quite good, producers buying raw materials in the local market, 83% of raw materials are directly processed, 17% of raw materials are not directly used, 67% of producers process raw materials in the morning, 33% in the evening before sales, 100% of traders take satay lilit without using gloves, and the cleanliness and personal hygiene of traders are still not good. Keywords : Sate lilit, E.coli, S. aureus, hygiene and sanitation